Dynare replication of "A Model of Secular Stagnation: Theory and Quantitative Evaluation" by Eggertsson et al. (2019) - Alex Crescentini; Federico Giri (Institute for Replication (I4R), 2023)
This paper replicates the study "A Model of Secular Stagnation: Theory and Quantitative Evaluation" by Eggertsson et al. (2019) using the Dynare toolkit. Replication is important as it confirms the results of the original article, provides a user-friendly version using Dynare (Adjemian et al., 2022), and shows how to deal with large-scale models with occasionally binding constraints. The results show that the original Matlab code was fully replicated, but minor discrepancies were found between the paper's equations and the code. The two models produce similar dynamics but with small differences, particularly at the beginning of the simulation.
Keywords: E0; E43; C62; 330; Dynare; Secular Stagnation; Occasionally Binding Constraints